1998
DOI: 10.1002/elps.1150190540
|View full text |Cite
|
Sign up to set email alerts
|

Improved protein solubility in two‐dimensional electrophoresis using tributyl phosphine as reducing agent

Abstract: In this study, dithiothreitol was replaced by tributyl phosphine as the reducing agent in both the sample solution for the first-dimensional isoelectric focusing and during the immobilised pH gradient (IPG) equilibration procedure. Tributyl phosphine improves protein solubility during isoelectric focusing, which results in shorter run times and increased resolution. Tributyl phosphine is nonionic and thus does not migrate in the IPG, therefore maintaining reducing conditions during the course of the first-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(125 citation statements)
references
References 14 publications
2
122
0
1
Order By: Relevance
“…Thiourea might have enhanced the solublization of the membranes or highly hydrophobic proteins in our samples, especially after mild sonication [22]. The solublization of membrane proteins is still the most challenging step in 2-DE-based proteomics approaches [23][24][25]. Nevertheless, the optimized protocol in this study resulted in a uniform spot distribution on a single protein map and we observed excellent reproducibility (Fig.…”
Section: -De Protocol and Reproducibilitymentioning
confidence: 66%
“…Thiourea might have enhanced the solublization of the membranes or highly hydrophobic proteins in our samples, especially after mild sonication [22]. The solublization of membrane proteins is still the most challenging step in 2-DE-based proteomics approaches [23][24][25]. Nevertheless, the optimized protocol in this study resulted in a uniform spot distribution on a single protein map and we observed excellent reproducibility (Fig.…”
Section: -De Protocol and Reproducibilitymentioning
confidence: 66%
“…A mixture composed of 0.5% Triton X-100 and 4% CHAPS was found to be the most efficient for solubilization of proteins. In order to improve the solubility of molecules, urea was replaced by a mixture of thiourea/urea (2 M/7 M), reported to have a much higher power of solubility (23), and DTT was replaced by tributylphosphine (5 mM), a more powerful reducing agent (24). However, these reagent modifications had no obvious benefit for the 2D maps.…”
Section: D Electrophoresis Of Drosophila Hemolymphmentioning
confidence: 99%
“…The focused strips were equilibrated in a solution containing 6 M urea, 30% glycerol, 50 mM Tris-HCl, pH 6.8, 5 mM TBP, and 2% SDS (w/v) for 20 min (Rabilloud et al, 1997;Herbert et al, 1998). Separation in the second dimension was conducted at room temperature on gradient Tricine-SDS gels (8 to 16% acrylamide) (Schägger and von Jagow, 1987).…”
Section: Two-dimensional Gel Electrophoresismentioning
confidence: 99%